Interactions between halotolerant nitrogen-fixing bacteria and arbuscular mycorrhizal fungi under saline stress - Ji, Chao; Ge, Yuhan; Zhang, Hua; Zhang, Yingxiang; Xin, Zhiwen; Li, Jian; Zheng, Jinghe; Liang, Zengwen; Cao, Hui; Li, Kun (Frontiers in Microbiology, 2024)
Background and aims Soil salinity negatively affects crop development. Halotolerant nitrogen-fixing bacteria (HNFB) and arbuscular mycorrhizal fungi (AMF) are essential microorganisms that enhance crop nutrient availability and salt tolerance in saline soils. Studying the impact of HNFB on AMF communities and using HNFB in biofertilizers can help in selecting the optimal HNFB-AMF combinations to improve crop productivity in saline soils. Methods We established three experimental groups comprising apple plants treated with low-nitrogen (0 mg N/kg, N0), normal-nitrogen (200 mg N/kg, N1), and high-nitrogen (300 mg N/kg, N2) fertilizer under salt stress without bacteria (CK, with the addition of 1,500 mL sterile water +2 g sterile diatomite), or with bacteria [BIO, with the addition of 1,500 mL sterile water +2 g mixed bacterial preparation (including Bacillus subtilis HG-15 and Bacillus velezensis JC-K3)]. Results HNFB inoculation significantly increased microbial biomass and the relative abundance of beta-glucosidase-related genes in the rhizosphere soil under identical nitrogen application levels (p < 0.05). High-nitrogen treatment significantly reduced AMF diversity and the relative abundance of beta-glucosidase, acid phosphatase, and urea-related genes. A two-way analysis of variance showed that combined nitrogen application and HNFB treatment could significantly affect soil physicochemical properties and rhizosphere AMF abundance (p < 0.05). Specifically, HNFB application resulted in a significantly higher relative abundance of Glomus-MO-G17-VTX00114 compared to that in the CK group at equal nitrogen levels. Conclusion The impact of HNFB on the AMF community in apple rhizospheres is influenced by soil nitrogen levels. The study reveals how varying nitrogen levels mediate the relationship between exogenous HNFB, soil properties, and rhizosphere microbes.